Ernst-von-Glasersfeld-Lectures 2015 - Hug, Theo; Schorner, Michael; Mitterer, Josef (innsbruck university press, 2015)
" The present volume documents the Ernst-von-Glasersfeld Lectures 2015 at the University of Innsbruck. In addition to the lectures by Siegfried J. Schmidt and Gebhard Rusch, two other contributions from the Ernst-von-Glasersfeld Archive are printed. These deal with documentary and media artistic intention with the Lana project and ""Yerkish"", the first sign language for primates, the philosopher and communication scientist Ernst von Glasersfeld (1917-2010) together with Piero Pisani beginning of the 70's at the University of Georgia developed."